Pengaruh Brand Awareness dan Word Of Mouth Terhadap Keputusan Pembelian Produk Makeup Somethinc Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Pancasila - Amelia, Della; Hermawati, Ati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the effect of brand awareness and word of mouth on purchasing decisions of Somethinc makeup products among students of the Faculty of Economics and Business at Pancasila University. This research employs a quantitative method with a correlational approach. The sampling technique used was purposive sampling, involving 95 respondents. Data were collected through questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that brand awareness has a positive and significant effect on purchasing decisions. Word of mouth also has a positive and significant effect on purchasing decisions. Furthermore, brand awareness and word of mouth simultaneously have a significant effect on purchasing decisions of Somethinc makeup products. This study concludes that increasing brand awareness and positive word of mouth can enhance students’ purchasing decisions toward Somethinc makeup products.